2007
DOI: 10.1037/0002-9432.77.2.324
|View full text |Cite
|
Sign up to set email alerts
|

Attachment patterns are associated with symptomatology and course of schizophrenia in male inpatients.

Abstract: The authors tested the hypotheses that the insecure attachment styles of adult patients with schizophrenia are associated with (a) diagnosis, (b) psychopathological syndromes, and (c) course of the disorder. Thirty schizophrenic and 30 age-matching control males answered a self-report questionnaire tapping secure, avoidant, and anxious/ambivalent attachment styles. The patients were diagnosed using the Structured Clinical Interview for DSM-IV (M. B. First, R. L. Spitzer, M. Gibbon, & J. B. W. Williams, 1995), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 72 publications
4
85
3
1
Order By: Relevance
“…Groh et al 2012), depression (Brumariu and Kerns 2010), and externalizing behaviour problems (Fearon et al 2010). Many separate studies support this effect for a list of other problems such as dissociation (Liotti 2006), eating pathology (Goossens et al 2012), non-suicidal self-injury (Bureau et al 2010), or even the symptomatology and course of schizophrenia (Ponizovsky et al 2007). As a consequence, insecure attachment is considered an important transdiagnostic risk factor in the development of psychopathology and could therefore be an important factor to take into account during the treatment of any child and adolescent emotional or behavioural disorder.…”
Section: Attachment Theorymentioning
confidence: 96%
“…Groh et al 2012), depression (Brumariu and Kerns 2010), and externalizing behaviour problems (Fearon et al 2010). Many separate studies support this effect for a list of other problems such as dissociation (Liotti 2006), eating pathology (Goossens et al 2012), non-suicidal self-injury (Bureau et al 2010), or even the symptomatology and course of schizophrenia (Ponizovsky et al 2007). As a consequence, insecure attachment is considered an important transdiagnostic risk factor in the development of psychopathology and could therefore be an important factor to take into account during the treatment of any child and adolescent emotional or behavioural disorder.…”
Section: Attachment Theorymentioning
confidence: 96%
“…High rates of insecure attachment styles have also been reported in people with psychosis (e.g. Couture et al, 2007;Ponizovsky, Nechamkin, & Rosca, 2007; MacBeth, Gumley, Schwannauer, & Fisher, 2011). Investigation of the mechanisms, such as attachment and affect regulation, by which early adversity can lead to psychiatric symptoms, will bring us closer to a complete psychological understanding of psychosis.…”
Section: Directions For Future Researchmentioning
confidence: 98%
“…Groups of people with psychosis (including chronic and first episode samples) show a high rate of insecure attachment styles (Dozier, Cue, & Barnett, 1994;Couture, Lecomte, & Leclerc, 2007;Dozier & Lee, 1995;Dozier, Stevenson, Lee, & Velligan, 1991), particularly of the avoidant type (MacBeth, Gumley, Schwannauer, & Fisher, 2011;Ponizovsky, Nechamkin, & Rosca, 2007;Berry, Barrowclough, & Wearden, 2008) (reviewed in Berry et al, 2007;Read & Gumley, 2008). Data are scarce regarding specific relationships of attachment styles with individual symptoms, but there is some evidence of a significant association between insecure attachment and paranoia (Berry, Wearden, Barrowclough, & Liversidge, 2006;Berry et al, 2008;MacBeth, Schwannauer, & Gumley, 2008).…”
Section: Attachment Theory and Psychosismentioning
confidence: 99%
“…A large and influential epidemiological study found evidence for an association between insecure adult attachment and schizophrenia (Mickelson et al, 1997), and although this association has been replicated in non-clinical (Berry et al, 2007b;Berry et al, 2006;Korver-Nieberg et al, 2014;Meins et al, 2008) and clinical samples (Berry et al, 2007a;Gumley et al, 2014;Korver-Nieberg et al, 2014;Korver-Nieberg et al, 2015;Ponizovsky et al, 2007;Ponizovsky et al, 2013) it has been suggested that it could be more informative to explore such associations in relation to specific symptoms of psychosis (Bentall, 2004). Such specificities can provide a clearer understanding of how certain psychological mechanism are meaningfully related to the experiences of individuals with psychosis (Bentall and Fernyhough, 2008) and, in turn this information may help clinicians focus psychological interventions appropriately.…”
Section: Introductionmentioning
confidence: 99%